The Russian Literary Language: From XVIII to XX Centuries (Филологический класс, 2009)
The article considers the historical processes associated with the development of Russian literary language. Theoretical principles are shown on the ground of poetic texts of XIX - XX centuries. It allows the author to select interesting trends together with the identification of the modern democratic process language.